Factors Influencing Network Marketers’ Entrepreneurial Performance - Salvador, Irene (Journal of Interdisciplinary Perspectives, 2025)
Network marketers often face significant challenges that impact their entrepreneurial performance and overall success. This study investigates how self-efficacy, entrepreneurial commitment, entrepreneurial orientation, and social cohesion influence the entrepreneurial performance of 316 purposively selected network marketers in Region XII, Philippines. Using a survey-based design, data were analyzed through regression to examine these relationships. Results show that self-efficacy, entrepreneurial commitment, and social cohesion positively affect entrepreneurial performance, with entrepreneurial orientation also playing a key role. These factors collectively explain 76% of the variation in entrepreneurial performance, highlighting their critical importance in driving increased production, new business establishment, higher sales, and greater profitability. The findings align with the Theory of Reasoned Action and the Expectancy Theory of Motivation, illustrating how these factors shape effort, persistence, and performance in network marketing. This study provides actionable insights for enhancing network marketers' performance and contributes to understanding the dynamics of multi-level marketing businesses.